The Effects of Work Motivation and Work Discipline on Employee Performance in a Public Service Organization - Sri Andayaningsih; Fahmiah Akilah; Sitti Marhumi; Nurinaya Nurinaya (Advances in Human Resource Management Research, 2026)
Purpose: This study examines the effects of work motivation and work discipline on employee performance at the Makassar City Public Water Utility Company. Research Method: A quantitative approach with a causal research design was employed. Data were collected through questionnaires distributed to employees selected using a simple random sampling technique. The data were analyzed using multiple linear regression with SPSS to assess the partial and simultaneous effects of work motivation and work discipline on employee performance. Results and Discussion: The results reveal that work motivation and work discipline have positive and significant effects on employee performance. Work motivation enhances employees’ commitment, enthusiasm, and work quality, while work discipline promotes compliance with organizational rules, punctuality, and consistency in task execution. Together, these factors significantly improve employee productivity and effectiveness, indicating that motivated and disciplined employees are more likely to achieve higher performance levels. Implications: Organizations should strengthen motivational programs and maintain effective disciplinary systems to improve employee performance, service quality, and organizational effectiveness, particularly in public service institutions. Originality: This study provides empirical evidence on the complementary roles of work motivation and work discipline in enhancing employee performance within a public utility organization, highlighting the importance of integrating motivational and disciplinary strategies in human resource management.